NURUDDIN ‘ITR'S HADITH MANHAJ: A SIGNIFICANT CONTRIBUTION TO THE DEVELOPMENT OF HADITH STUDIES - Siregar, Ilham Ramadan (Jurnal Studi Hadis Nusantara, 2024)
This study aims to comprehensively examine Nuruddin ‘Itr’s methodology in Manhaj ‘Ulum al-Hadith, both from a methodological perspective and its implications for the development of hadith studies today. Through this research, it is expected to gain a deeper understanding of how Nuruddin ‘Itr’s methodology provides solutions to various challenges in modern hadith studies. One of his contributions to the field is that Shaykh Nuruddin ‘Itr offers a systematic and comprehensive approach to hadith criticism. Nuruddin 'Itr defines hadith as everything attributed to the Prophet Muhammad saw., whether in the form of words, actions, or approvals, with the criteria for an authentic hadith (sahih) including a continuous chain of transmission (sanad), the justice and precision of the narrators, and being free from contradictions (shadh) and defects ('illah). He emphasizes that authentic hadith must be followed, while the application of solitary (ahad) and weak (da'if) hadith requires caution, especially in matters of creed and law. Although the official codification of hadith began after the Prophet’s time, its authenticity has been preserved through a rigorous scientific methodology. Nuruddin 'Itr also highlights the importance of sincerity and ethics in studying and transmitting hadith, as well as the need to adapt teaching methods to remain relevant in modern times.